MENUNDA KEHAMILAN KARENA AKADEMIK DAN EKONOMI: TINJAUAN MAQASHID SYARIAH PADA MAHASISWA STDIIS JEMBER - Muadz; Musyafi Usman (LPPM STAI Muhammadiyah Probolinggo, 2025)
Delaying pregnancy is a choice often made by young couples, especially students, who face economic and academic challenges. This study aims to identify the economic and academic considerations in the decision to delay pregnancy among student couples at STDI Imam Syafi’i Jember and to analyze this decision from the perspective of maqashid sharia. A qualitative method with in-depth interviews was used to explore the reasons and impacts of this decision. The results show that unstable economic conditions and academic burdens are the main factors influencing pregnancy postponement. Couples strive to balance their responsibilities as students and parents to maintain the quality of family life. From the maqashid sharia perspective, this decision aligns with the principles of preserving five main objectives of Islamic law, particularly the protection of life, wealth, intellect, and lineage. Delaying pregnancy does not imply permanently limiting offspring but managing birth spacing for the welfare of the family.